Officer Buckle And Gloria - Peggy Rathmann (U.S.A Scholastic Inc., 1995)
The children at Napville Elementary School always ignore Officer Buckle's safety tips, until a police dog named Gloria accompanies him when he gives his safety speeches.
The Caldecott Medal